Google Meet and Google Classroom on Learning History: Review from Students Perspective - Marian, Ayuhel Letrik; Umasih; Sarkadi (Journal of Education Reseach and Evaluation, 2023)
Changes in the learning process require teachers to be more creative and innovative in delivering learning. The effectiveness of online learning needs to be considered, by utilizing various platforms, including using Google Classroom and Google Meet in history learning. This study aims to analyze the students' perspectives are related to the effectiveness of the platforms used during distance learning. The method used in this research is descriptive with a quantitative approach. Respondents in this study were 39 active students, eleventh grade. Data was collected using an online questionnaire via Google Form. The results of this study indicate that as many as 81.3% of students stated that they were motivated to take part in learning because it did not require a lot of quota, and the features used on the platform were very easy to operate and very attractive. Meanwhile, 18.7% of respondents stated that they were not interested in the platforms used in online learning and needed an alternative platform. From this it appears that in general these two platforms are one of the right choices to use, which is not only appropriate for the suitability of the material, or with the characteristics of students, but also the right platform because it does not require too much of a large quota load but is sufficient in online usage that does not burdensome students.